The notes on rotational surfaces in Galilean space - Almaz, Fatma; Kulahci, Mihriban Alyamac (World Scientific Publ Co Pte Ltd, 2021)
In this study, we provide a brief description of rotational surfaces in 4-dimensional (4D) Galilean space using a curve and matrices in G4. That is, we provide different types of rotational matrices, which are the subgroups of M by rotating a selected axis in E4. Hence, we choose two parameter matrices groups of rotations and we give the matrices of rotation corresponding to the appropriate subgroup in Galilean 4-space and we generate rotated surfaces.
Keywords: Galilean space; rotated surfaces; killing vector field